Blood pressure levels post mechanical thrombectomy and outcomes in large vessel occlusion strokes. (8th August 2017) - Goyal, Nitin; Tsivgoulis, Georgios; Pandhi, Abhi; Chang, Jason J.; Dillard, Kira; Ishfaq, Muhammad Fawad; Nearing, Katherine; Choudhri, Asim F.; Hoit, Daniel; Alexandrov, Anne W.; Arthur, Adam S.; Elijovich, Lucas; et al.
Abstract : Objective: There are limited data evaluating the effect of post mechanical thrombectomy (MT) blood pressure (BP) levels on early outcomes of patients with large vessel occlusions (LVO). We sought to investigate the association of BP course following MT with early outcomes in LVO. Methods: Consecutive patients with LVO treated with MT during a 3-year period were evaluated. Hourly systolic BP (SBP) and diastolic BP (DBP) values were recorded for 24 hours following MT and maximum SBP and DBP levels were identified. LVO patients with complete reperfusion following MT were stratified in 3 groups based on post-MT achieved BP goals: <140/90 mm Hg (intensive), <160/90 mm Hg (moderate), and <220/110 mm Hg or <180/105 mm Hg when pretreated with IV thrombolysis (permissive hypertension). Three-month functional independence was defined as modified Rankin Scale score of 0–2. Results: A total of 217 acute ischemic stroke patients with LVO were prospectively evaluated. A 10 mm Hg increment in maximum SBP documented during the first 24 hours post MT was independently ( p = 0.001) associated with a lower likelihood of 3-month functional independence (odds ratio [OR] 0.70; 95% confidence interval [CI] 0.56–0.87) and a higher odds of 3-month mortality (OR 1.49; 95% CI 1.18–1.88) after adjusting for potential confounders. In addition, achieving a BP goal of <160/90 mm Hg during the first 24 hours following MT was independently associated with a lower likelihood of 3-month mortality (OR 0.08; 95% CI 0.01–0.54; p = 0.010) in comparison to permissive hypertension. Conclusions: High maximum SBP levels following MT are independently associated with increased likelihood of 3-month mortality and functional dependence in LVO patients. Moderate BP control is also related to lower odds of 3-month mortality in comparison to permissive hypertension.